Successful non‐operative management of traumatic extrahepatic portal venous injury without intraperitoneal hemorrhage: a case report - Hamanaka, Kunio (Acute Med Surg, 2016)
CASE: A 52‐year‐old woman was admitted to our hospital with hypotension after falling from the fifth floor of an apartment building. Contrast‐enhanced computed tomography showed liver injury with extravasation of contrast material from the hepatic artery, and extrahepatic portal venous injury with extravasation and pseudoaneurysm. Intra‐abdominal hemorrhage was not observed, and bleeding was confined to the retroperitoneal space. Hepatic arteriography showed extravasation, while portal venography showed pseudoaneurysm but no extravasation. After transarterial embolization, the patient's vital signs improved. Non‐operative management was selected for the portal venous injury. OUTCOME: Computed tomography on the 58th hospital day revealed disappearance of the portal venous pseudoaneurysm. The patient was discharged on the 90th hospital day without any complications. CONCLUSION: This case shows that non‐operative management can be selected for portal venous injury when there is no retroperitoneal injury and bleeding is confined to the retroperitoneal space.